Report of the Hospital Sub-committee - Horder, Thomas, 1871-1955 (London : Institutional Management Association)
1943-09-11 1943 1940s 15 pages a teaching hospital staffed by experienced dietitians and supplied with lecturers from the staff of the hospital and medical school. The course should cover one year or eighteen months, it should include not less than:— i. Tuition. — 120 Lectures on:— Diet in health and disease; Applied physiology and anatomy; Chemical and medical subjects; Hospital etiquette and ward procedure. Tuition should be given in hospital bio-chemistry in the bio-chemical department of the hospital (blood sugars, urine analysis, metabolic tests, etc.). ii. Practical Work:— Six months spent in special diet kitchens including visits to patients. Six week's full time (or equivalent number of part-time hours) in the Out-Patients' Department helping to teach the patients how to carry out their diets at home. One month's full time in the Catering Department of the hospital. This training meets with the requirements for membership of the British Dietetic Association. 3. Suggested Conditions for Working and Living. 1. Residence i. For all residents, living conditions should, where possible, compare favourably with home life as approximately 10/12th of the working life of those who take employment in residential insitutions [institutions] is spent at their place of work. ii. It is advisable for the professional domestic staff to be resident, but in buildings adjacent to rather than in the hospital. iii. Provided that the senior staff were given proper status and conditions they in turn would be interested in the living conditions of those for whom they were responsible and so effect any necessary improvements. Accommodation:— Domestic Administrator: Working — office. Living — bedroom and sitting room or bedsitting room. Assistant Administrator: Working — office. Living — bedroom and sitting room or bedsitting room. 7 292/842/2/104